A national cross-sectional survey of health literacy of caregivers attending Canadian pediatric emergency departments. - Manasi Rajagopal; Samina Ali; Keon Ma; Maryna Yaskina; Andrea Morrison; Kurt Schreiner; Julie Leung; Shannon Scott; Darcy Beer; Paul Clerc; Tyrus Crawford; Serge Gouin; et al. (PLoS ONE)
Background Health literacy assessment is key to better meeting family needs and developing informed strategies to promote positive health outcomes for children. The objective of this study was to describe the health literacy of caregivers who use Canadian pediatric emergency departments and relate it to demographic and visit-specific variables. Methods This study utilized a descriptive, cross-sectional survey design with medical record review. A bilingual survey was electronically administered to caregivers presenting to 10/15 Canadian pediatric emergency departments. Health literacy was assessed using the Newest Vital Sign tool. Results 1957 caregivers completed the Newest Vital Sign assessment. Caregivers' mean age was 37.8 ± 7.7 years, 74.3% (1449/1950) were mothers and 51.9% (993/1912) had a university/professional degree. 12.0% (235/1957) had a high likelihood of limited health literacy, 16.5% (323/1957) had possible limited health literacy and 71.5% (1399/1957) demonstrated adequate health literacy. Adequate health literacy scores were associated with having a university/professional degree [aOR 1.47 (95% CI 1.11-1.94)] and having a household annual income of over $25,000 [aOR 4.10 (2.66-6.31)]; they were inversely associated with having a total of 4 or more children [aOR 0.61 (0.40-0.91)] and having a main language at home other than English or French [aOR 0.32 (0.23-0.43)]. Interpretation With over 1/4 caregivers facing health literacy challenges, health care providers in emergency departments must be cognizant of their communication and education approach when caring for families and providing at-home care guidance. Clinicians should consider applying health literacy principles to all family encounters to help address healthcare disparities.